ANALISIS OPTIMALISASI NILAI THRUST, TORQUE DAN EFFICIENCY PROPELLER B SERIES DAN KAPLAN SERIES PADA STUDI KASUS KAPAL PENCALANG 15 GT MENGGUNAKAN METODE CFD - Muhammad Iqbal; Abdul Gafur; Bambang Antoko (Proceedings Conference on Marine Engineering and its Application, 2023)
Pencalang is a traditional sailing ship used as a merchant ship. Along with the times,Pencalang changed its function to become a patrol boat with the addition of a motor as its drivingforce. In the traditional wooden ship revitalization project, propeller selection is important because theship uses a sail and motor system. This research analyzes the use of Kaplan propeller types to optimizethrust, torque, and efficiency where currently the propeller used for Pencalang ships is type B-series.The selection of the Kaplan propeller to be analyzed is based on the diameter that matches theavailability of propeller space on the propeller ship or < Dpropeller B-series g. The selection of kaplanpropellers resulted in kaplan types K4-55 and K4-70 with diameters of 0.659 and 0.619, respectively.The B-series and kaplan series propellers that have been selected are then analyzed using modelingsoftware and simulation software that has calculated its error using MAPE with the result of an error< 10%. The simulation results in the software show that the Kaplan series propeller can be used as anoption for the type of propeller that can be used on Pencalang if a propeller replacement will be carriedout later, because with a smaller diameter compared to the B-series propeller it will produce greaterthrust and torque. The Kaplan series propeller that produces the highest thrust and torque is K4-70with a maximum thrust value of 6966.76 N and a maximum torque of 978.977 Nm.